Synthesis of high-surface-area ruthenium oxide aerogels by non-alkoxide sol-gel route - Suh, DJ; Park, TJ; Kim, WI; Hong, IK (ELSEVIER, 2003)
High-surface-area ruthenium oxide aerogels with pronounced mesoporosity are prepared by carbon dioxide supercritical drying of alcogels by a non-alkoxide sol-gel process with ruthenium chloride as a precursor and epoxide as a proton scavenger. The influence of various sol-gel preparation parameters both on gel formation and the textural properties and voltammetric response of the resulting ruthenium oxide aerogels are investigated systematically. The un-calcined ruthenium oxide aerogel in the amorphous phase possesses a surface area in excess of 350m(2) g(-1) has a specific capacitance as high as 595 F g(-1). (C) 2002 Elsevier Science B.V. All rights reserved.